Web-Based Auction System with Dual-Authentication for Syarikat Perniagaan Fong Yuen Sdn. Bhd. - Chong, Zhi Qi; Sapiee Jamel, (Applied Information Technology And Computer Science, 2023)
Effective sales techniques are essential for business success, and auctions offer a quick and mutually beneficial approach to buying and selling. Syarikat Perniagaan Fong Yuen Sdn. Bhd., a furniture provider based in Kulai, Johor, Malaysia, faces challenges in their sales process. To address the issue of lengthy negotiations causing transaction delays, a web-based auction system is proposed. This system will enable the company to conduct product auctions, simplifying the negotiation process and reducing transaction delays. The system will feature easy registration, bidding, and payment processes for customers, improving the overall user experience. Following the prototyping model, the system will undergo iterative improvements based on user feedback. Security is a top priority, with dual-authentication implemented to ensure the safety of the system for administrators and bidders. The ultimate objective is to establish a secure and efficient platform that streamlines the sales process, benefiting both company and its customers.